Bioversity International nutrition strategy 2011-2021: Resilient food and nutrition systems: analyzing the role of agricultural biodiversity in enhancing human nutrition and health - Bioversity International (2011)
Bioversity International’s nutrition research over the past several years has focused on the role and impact of traditional foods on dietary diversity and livelihoods. The research agenda is being expanded under Bioversity’s 2011-2021 Nutrition Strategy to develop strong methodological and empirical evidence on how agricultural biodiversity contributes to dietary diversity and nutrition with downstream livelihood and ecosystem benefits. The new strategy focuses on food and nutritional system approaches to improving human nutrition and health. The major goal of the strategy and subsequent programme is to promote the use of agricultural biodiversity within food production systems and provide nutritionally-rich food sources that contribute to dietary diversity and, potentially, better nutrition and health. Our major focus is in rural and peri-urban communities in the developing world.[Text taken from the book]